Revista ACB Vol. 19, n. 1 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Revista ACB Vol. 19, n. 1 (2014) Link de acesso ao númerohttp://revista.acbsc.org.br/racb/issue/view/53